Clay mineral assemblages in a sediment core KX21-2 - Jiawang Wu; Zhifei Liu; Chao Zhou (PANGAEA, 2022)
Clay mineralogy data of late-Quaternary marine sediment cores in the western equatorial Pacific are presented here. These include core KX21-2 collected on the Ontong Java Plateau (downcore profile over the past 380 ka), as well as cores KX10-1, KX12-1, KX13-1 and KX15-2 collected off the northern coast of Papua New Guinea (surface samples only). All the five cores were retrieved a giant gravity corer onboard R/V Kexue-1 during the KX08-973 cruise in 2008/2009. The Clay minerals were identified by X-ray diffraction (XRD) using a PANalytical X extquotesinglePert Pro diffractometer, with a 0.03°2Q/s rate under CuKa radiation and Ni filter, at Tongji University. The analysis was conducted on oriented mounts of non-calcareous, clay-sized particles (<2 mm). The XRD runs were performed under three conditions: untreated, glycolated (in ethylene-glycol vapor for 24 h), and heated (490 °C for 2 h). Identification of clay minerals was done according to a comprehensive comparison of the three XRD diagrams. For the main clay-mineral groups, the relative abundances were calculated by measuring the peak areas on glycolated curve using MacDiff 4.2 software. For more details see the reference paper.
In: Wu, J et al. (2022): Late Quaternary clay mineral assemblages in the Western Pacific Warm Pool [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.946134